Theoretical basis of european integration - Яковюк, І. В. (Theory and practice of jurisprudence, 2016)
The article is devoted to the research in theoretical basis of European integration. The stated problem is not quite studied in the domestic legal science that determines its actuality. The article marks out definite sequence of stages (preferential trade agreements → free trade area → custom’s union → common market → monetary union → political integration) which characterize orientation of European integration. The main approaches to the definition of European integration are studied and its features are marked out (the EU is distinguished from the rest of the world and relatively separates from it; the EU institutional mechanism comprises supranational and intergovernmental institutions, balance of powers of which is determined by the tasks of the stated stage of integration; the EU is based on supranational law which is the background for regional legal system forming; clear definition of the aims and tasks of integration is typical for the EU and, correspondently, there is definite consequence of carried stages of integration of socio-economic and political-legal systems of the Member States). The author specifies the system of criteria which allows comparing different intergovernmental units: matching a region as the subject which possesses legal subjectiveness; existence of the system of common values as the basis for regional identity formation; socio-economic homogeneity of the Member States; formation of the institutional mechanism with the elements of supranationality; compliance with consequence of the integration stages; developed law of the community; providing synchronization of the processes of socio-economic and political integration; realization of coordinated and ideally, common foreign and defense policy. On the basis of the analysis the conclusion about the unifying initiatives spreading on the different countries of different world regions in the end of the XXth century was made. Integration has become one of the basis, and simultaneously objectization of changes in the governmental-legal development of these countries. At the same time integration characteristics of the EU are not always intrinsical to other integration units, and this generates methodological problem for their comparison. Key words: European integration, the concept and characters of European integration, the European Union.